Black Hibiscus African Americans and the Florida imaginary - Lowe, John Wharton (University Press of Mississippi, 2024)
Explores Florida's colonial past, focusing particularly on interactions between maroons who escaped enslavement, and on Albery Whitman's The Rape of Florida, which also links Black people and Native Americans. Contributors consider film, folklore, and music, and key Black writers